2007
DOI: 10.1105/tpc.106.048199
|View full text |Cite
|
Sign up to set email alerts
|

SLocus Genes and the Evolution of Self-Fertility inArabidopsis thaliana

Abstract: Loss of self-incompatibility (SI) in Arabidopsis thaliana was accompanied by inactivation of genes required for SI, including S-LOCUS RECEPTOR KINASE (SRK) and S-LOCUS CYSTEINE-RICH PROTEIN (SCR), coadapted genes that constitute the SI specificity-determining S haplotype. Arabidopsis accessions are polymorphic for CSRK and CSCR, but it is unknown if the species harbors structurally different S haplotypes, either representing relics of ancestral functional and structurally heteromorphic S haplotypes or resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
115
3
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 42 publications
7
115
3
3
Order By: Relevance
“…Previous studies had shown that in some accessions, such as C24, the SRK and SCR sequences are highly decayed or deleted, and only partial remnants of these sequences have been retained . In other accessions, SRK sequences are relatively well preserved while SCR sequences are very much degraded or entirely absent (Nasrallah et al 2004;Sherman-Broyles et al 2007). For example, in SA-containing accessions, SCRA sequences are nonfunctional and may be repeated, truncated, or rearranged (Nasrallah et al 2004;Sherman-Broyles et al 2007;Boggs et al 2009a), while the SRKA gene has remained much more intact, being transcribed but encoding a truncated open reading frame due to splice site usage as in the Col-0 accession (Kusaba et al 2001;Shimizu et al 2004;Tang et al 2007), or even remaining functional as in the Wei-0 accession (Tsuchimatsu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies had shown that in some accessions, such as C24, the SRK and SCR sequences are highly decayed or deleted, and only partial remnants of these sequences have been retained . In other accessions, SRK sequences are relatively well preserved while SCR sequences are very much degraded or entirely absent (Nasrallah et al 2004;Sherman-Broyles et al 2007). For example, in SA-containing accessions, SCRA sequences are nonfunctional and may be repeated, truncated, or rearranged (Nasrallah et al 2004;Sherman-Broyles et al 2007;Boggs et al 2009a), while the SRKA gene has remained much more intact, being transcribed but encoding a truncated open reading frame due to splice site usage as in the Col-0 accession (Kusaba et al 2001;Shimizu et al 2004;Tang et al 2007), or even remaining functional as in the Wei-0 accession (Tsuchimatsu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the Lz-0 SC haplotype was compared to that of the previously characterized C24 SA-SC recombinant haplotype ( Figure 1B; Sherman-Broyles et al 2007), the Col-0 SA haplotype ( Figure 1C; Kusaba et al 2001), and the Cvi-0 SB haplotype ( Figure 1D; Tang et al 2007). Among these S haplotypes, the Lz-0 S haplotype has the longest PUB8-ARK3 region (.44 kb).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S locus (Sherman-Broyles et al 2007), suggesting that this element might have a widespread role in the evolution of self-compatibility.…”
Section: Discussionmentioning
confidence: 99%